Essential Excel 2016 : a step-by-step guide - Slager, David (Apress, 2016)
This book shows you how easy it is to create, edit, sort, analyze, summarize and format data as well as graph it. Loaded with screen shots, step-by-step instructions, and reader exercises, Essential Excel 2016 makes it easy for you to get to grips with this powerful software and what it can do.What You'll LearnHow to create amazing visualizations of your dataEasy and accurate methods for entering dataHow to extract just the information you want from imported data, and manipulate it and format it the way you wantExport your results to other programs or share with others in the cloudOrganize, Summarize, Filter, and Consolidate your Data in almost any way imaginableAudit, Validate and Protect your DataWho This Book Is ForAnyone new to Excel, or looking to take better advantage of the platform and find out its latest features